Avoidant/restrictive food intake disorder, other eating difficulties and compromised growth in 72 children: background and associated factors - Johansson, Maria; Hermansson, Jonas; Linnsand, Petra; Gillberg, Christopher; Nygren, Gudrun (Frontiers in Child and Adolescent Psychiatry, 2023)
This is a study of avoidant/restrictive food intake disorder (ARFID), other feeding disorders, and background factors, including seventy-two children (thirty-one girls, forty-one boys, aged 4–178 months) referred to a secondary/tertiary feeding service for eating difficulties and/or compromised growth. An in-depth review of their medical records was performed. Diagnostic criteria for ARFID were met in 26% of cases. Children with ARFID were older, more nutritionally deficient, and psychosocially impaired, and their feeding difficulties were less likely to go into remission. Most children's onset of feeding difficulties occurred during the first year of life. Several medical and/or psychosocial and/or neurodevelopmental background factors were often recorded in the same child, regardless of the presence of ARFID or not. Neurodevelopmental disorders were significantly more common in children with ARFID. In conclusion, feeding difficulties in children are often complex, with several associated factors. In a clinical setting, such as the present study, ARFID can be expected in about one-fourth of cases. The feeding difficulties in children with ARFID can be expected to be more severe and persistent than other feeding difficulties. Healthcare providers should be aware of possible underlying neurodevelopmental difficulties in children with ARFID.